Government Support During Pandemic in Developing Countries: A Case Study from Central Sulawesi Province, Indonesia - Irwan Waris; Ani Susanti; Muhammad Ahsan Samad (Migration Letters, 2023)
The problem of this research is how effective is the government support provided by developing countries, with special emphasis on Central Sulawesi Province in Indonesia, during the COVID-19 pandemic. This study aims to analyze various aspects of government preparedness in Central Sulawesi, assess the impact of this preparedness on community resilience, and identify key factors influencing the effectiveness of government support. Research sample consisted of employees of the Central Sulawesi Provincial Health Office bureaucracy who took part in a questionnaire survey. A questionnaire survey was conducted on a sample of 162 public service employees during the pandemic to identify respondents’ perceptions of the importance of the proposed indicators. This study uses quantitative research methods, using regression analysis with SPSS software and structural equation model (SEM) to determine a significant relationship between government support, bureaucracy, and resilience. Data analysis techniques include descriptive analysis, bivariate correlation, confirmatory factor analysis (CFA), and regression. The findings show a significant relationship between government support, resilience, and bureaucracy. While the bureaucracy in Central Sulawesi demonstrated the ability to make quick and informed decisions during the pandemic crisis, this study highlights the need for better coordination and collaboration among employees. The novelty of this study lies in its comprehensive analysis of city government preparedness levels and an innovative approach to examining the relationship between government preparedness and community resilience using regression analysis and SEM.